Conjunctival Lymphangiogenesis Was Associated with the Degree of Aggression in Substantial Recurrent Pterygia. (28th January 2016) - Zhao, Wei; Wang, Tao; Deng, Juan; Zhong, Lei; Huang, Weilan; Ling, Shiqi
Abstract : Objective . To examine conjunctival lymphatic vessels and to analyze the relationship between lymphangiogenesis and aggressive recurrent pterygia. Methods . Tissues from 60 excised recurrent (including 19 of Grade 1, 28 of Grade 2, and 13 of Grade 3) pterygia were used in the study. Tissues from 9 nasal epibulbar conjunctivae segments were used as controls. Pterygium slices from each patient were immunostained with LYVE-1 monoclonal antibodies to identify lymphatic microvessels in order to calculate the lymphovascular area (LVA), the lymphatic microvessel density (LMD), and the lymphovascular luminal diameter (LVL). The relationship between lymphangiogenesis (LVA, LMD, and LVL) and pterygium aggression (width, extension, and area) was clarified. Results . Few LYVE-1 positive lymphatic vessels were found in the normal epibulbar conjunctiva segments. Lymphatic vessels were slightly increased in Grades 1 and 2 and were dramatically increased in Grade 3 recurrent pterygia. The LMD was correlated with the pterygium area in Grade 1 and 2 pterygia. In Grade 3, both LVA and LMD were significantly correlated with the pterygium area. Conclusions . Lymphangiogenesis was associated with the degree of aggression in recurrent pterygia, particularly in substantial Grade 3 recurrent pterygia.